Merging of Thin‐ and Thick‐Film Fabrication Technologies: Toward Soft Stretchable "Island–Bridge" Devices. Issue 4 (15th February 2017) - Mohan, A. M. Vinu; Kim, NamHeon; Gu, Yue; Bandodkar, Amay J.; You, Jung‐Min; Kumar, Rajan; Kurniawan, Jonas F.; Xu, Sheng; Wang, Joseph
Abstract : Soft stretchable thick–thin‐film devices are prepared by merging different fabrication technologies with different functional materials. The new "island–bridge" devices rely on screen‐printed thick‐film island electrodes, connected by thin‐film serpentine interconnects. Such a hybrid fabrication process enables to realize high‐performance stretchable materials toward a new class of soft electronics with new capabilities that cannot be achieved via individual fabrication routes.